2017
DOI: 10.1002/ajp.22684
|View full text |Cite
|
Sign up to set email alerts
|

High mortality associated with tapeworm parasitism in geladas (Theropithecus gelada) in the Simien Mountains National Park, Ethiopia

Abstract: Despite increasing appreciation for parasitism as an important component of primate ecology and evolution, surprisingly few studies have demonstrated the costs of helminth parasitism in primates. Detecting parasite-related costs in primates is particularly difficult because it requires detailed, long-term data on individual host reproductive success, survival, and parasitism. The identification of the larval tapeworm Taenia serialis in geladas under intensive long-term study in the Ethiopian Highlands (Nguyen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Helminth parasites can have major consequences for host fitness and health, by reducing host fecundity (e.g., Budischak et al 2017;Akinyi 2019), decreasing survival (e.g., Schneider-Crease et al 2017), and increasing susceptibility to infection by other parasites (e.g., Ezenwa et al 2010). These costs are especially important in the context of male behavior and life histories because male reproductive effort should have major consequences for individual infection risk (Lee 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Helminth parasites can have major consequences for host fitness and health, by reducing host fecundity (e.g., Budischak et al 2017;Akinyi 2019), decreasing survival (e.g., Schneider-Crease et al 2017), and increasing susceptibility to infection by other parasites (e.g., Ezenwa et al 2010). These costs are especially important in the context of male behavior and life histories because male reproductive effort should have major consequences for individual infection risk (Lee 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, two extant subspecies are recognized within Theropithecus gelada–Theropithecus gelada gelada Rüppell, 1835 and Theropithecus gelada obscurus , Heuglin, 1863, but their validity and geographic distributions are unclear [ 18 – 24 ]. Although geladas have been the subjects of several, intensive behavioural studies (e.g., [ 25 – 27 ]), their intra-specific phylogenetic relationships remain unresolved [ 28 – 30 ]. According to IUCN, T .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as the dogs seem to be the primary source of infection for intermediate hosts, we highlight the importance of controlling the access of dogs in the recuse centers, as larval T. serials can seriously impact the health and welfare of primates. Dunbar (1980) and Schneider-Crease et al (2017a) have shown that the parasitism with larval T. serialis is an important cause of adult and infant mortality in wild geladas. Nguyen et al (2015) demonstrated also a decreased reproductive success in wild geladas infected with larvae of T. serialis .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence in a gelada population from Ethiopia varied according to the age group from 3.2 to 24.1%, with adults being more commonly affected (Dunbar, 1980). In another study, the overall prevalence was 14%, with adults and females more commonly affected than young and males, respectively (Schneider-Crease et al, 2017a). The overall average prevalence (evaluated as “visible swellings”) in the gelada population was 9.8% and 10.6%, in two studies performed in two different seasons (Dunbar, 1980).…”
Section: Discussionmentioning
confidence: 99%